2010
DOI: 10.17221/81/2009-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus on celery growth and nutrient uptake under different calcium and magnesium levels in substrate culture

et al.

Abstract: Li Y., Wang T., Li J., Ao Y., 2010. Effect of phosphorus on celery growth and nutrient uptake under different calcium and magnesium levels in substrate culture. Hort. Sci. (Prague), 37: 99-108.A greenhouse pot experiment was performed to study the effect of phosphorus (P) on celery (Apium graveolens L.) growth, quality and nutrient uptake under different calcium (Ca) and magnesium (Mg) levels in substrate culture. Results showed that there were significant interactions between P and the level of Ca and Mg in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
4
17
0
2
Order By: Relevance
“…3 and 4, Table 2). It has been reported that Ca 2+ and phosphorus addition in the growth medium enhanced the plant growth and yield (Ma et al 1994;Li et al 2010). The lowest grain/paddy and straw yields of wheat and rice crops were obtained from the control plants ( Figs.…”
Section: Discussionmentioning
confidence: 89%
“…3 and 4, Table 2). It has been reported that Ca 2+ and phosphorus addition in the growth medium enhanced the plant growth and yield (Ma et al 1994;Li et al 2010). The lowest grain/paddy and straw yields of wheat and rice crops were obtained from the control plants ( Figs.…”
Section: Discussionmentioning
confidence: 89%
“…In this respect, the high ash content in leaves may be correlated with the content of Ca and Mg, which predominantly accumulate in leaves [29]. Other investigations reported the significant influence of P, Ca and Mg supply on celery leaf elemental composition [30].…”
Section: Content Of K Zn Mn Fe Cu and Se In Plant Partsmentioning
confidence: 89%
“…The effects of poor nutrition, be it through infertile soils or incorrect soil pH level, directly affect the production of chlorophyll molecules resulting in chlorosis of leaves and a reduced photosynthetic rate, thus inhibiting some biological processes and decreasing the general health of the plants [23][24][25]. There are plausible mechanisms through which the production of chlorophyll could be affected, for example, the pH level of a growing medium affects the uptake of P [26] and the P level influences the nutrient uptake by plants [27]. The relationship between the nutrient P and chlorophyll is not fully understood.…”
Section: Introductionmentioning
confidence: 99%